CAUSES OF THE EMERGENCE OF NON-PERFORMING LOANS IN COMMERCIAL BANKING PRACTICE (American Journal of Business Management, Economics and Banking, 2025)
This paper examines the organizational and procedural approaches used by commercial banks to manage non-performing loans (NPLs). It highlights the role of specialized internal units—such as departments or divisions—dedicated to monitoring overdue debts, implementing debt rehabilitation strategies, and managing borrower assets. The study outlines a comprehensive set of measures used to improve the quality of distressed loans, including additional collateral, state guarantees, asset sales, and legal enforcement mechanisms. Furthermore, it discusses early intervention strategies, such as negotiating with borrowers and restructuring management, as well as various recovery methods like debt restructuring, refinancing, and debt sale to third parties. The paper emphasizes that banks select appropriate recovery strategies based on financial efficiency, transaction costs, risk exposure, reputational considerations, and the expected financial outcomes. Overall, the research provides insights into how banks can mitigate credit risk and maintain financial stability by effectively managing problem loans.